Adoptive cell therapy in multiple Myeloma. (2nd December 2017) - Vallet, Sonia; Pecherstorfer, Martin; Podar, Klaus
ABSTRACT: Introduction : Recent breakthrough advances in Multiple Myeloma (MM) immunotherapy have been achieved with the approval of the first two monoclonal antibodies, elotuzumab and daratumumab. Adoptive cell therapy (ACT) represents yet another, maybe the most powerful modality of immunotherapy, in which allogeneic or autologous effector cells are expanded and activated ex vivo followed by their re-infusion back into patients. Infused effector cells belong to two categories: naturally occurring, non-engineered cells (donor lymphocyte infusion, myeloma infiltrating lymphocytes, deltagamma T cells) or genetically- engineered antigen-specific cells (chimeric antigen receptor T or NK cells, TCR-engineered cells). Areas covered : This review article summarizes our up-to-date knowledge on ACT in MM, its promises, and upcoming strategies to both overcome its toxicity and to integrate it into future treatment paradigms. Expert opinion : Early results of clinical studies using CAR T cells or TCR- engineered T cells in relapsed and refractory MM are particularly exciting, indicating the potential of long-term disease control or even cure. Despite several caveats including toxicity, costs and restricted availability in particular, these forms of immunotherapy are likely to once more revolutionize MM therapy.